Developing The Evaluation Scale of Female School Administrators - Emel Tüzel İşeri (International Journal of Asian Education, 2021)
The aim of this study is to present a measurement tool that will be used to measure the female stereotypes faced by women managers in the school organization, how women managers are perceived and how teachers evaluate the school administrators. The study group consisted of 221 teachers working in primary schools in Ankara. As a result of the analysis, a measurement tool consisting of 45 items and five sub-factors including “General Management Success”, “Authority Provision and Impact on Interpersonal Relations”, “Personality Characteristics”, “Family Life” and “Objectivity and Equal Treatment” has been introduced. The Cronbach Alpha reliability coefficients of the factors were calculated as. 96, .94, .93, .94, .90 and. 98 for all items. The variances explained by the factors were 19.797%, 13.190%, 12.529%, 12.127% and 11.122% respectively. The total variance of the five factors was determined as 68.765%. The results show that the scale structure has been validated and that can be used as a valid and reliable tool in determining the evaluations of teachers among female school administrators.